Cybersecurity and resilience in the Arctic - Trump, Benjamin D.; Hossain, Kamrul; Linkov, Igor (NATO science for peace and security series. Information and communication security, 2020)
Until recently, the Arctic was almost impossible for anyone other than indigenous peoples and explorers to traverse. Pervasive Arctic sea ice and harsh climatological conditions meant that the region was deemed incapable of supporting industrial activity or a Western lifestyle. In the last decade, however, that longstanding reality has been dramatically and permanently altered. Receding sea ice, coupled with growing geopolitical disputes over Arctic resources, territory, and transportation channels, has stimulated efforts to exploit newly-open waterways, to identify and extract desirable resources, and to leverage industrial, commercial, and transportation opportunities emerging throughout the region.00This book presents papers from the NATO Advanced Research Workshop (ARW) Governance for Cyber Security and Resilience in the Arctic. Held in Rovaniemi, Finland, from 27-30 January 2019, the workshop brought together top scholars in cybersecurity risk assessment, governance, and resilience to discuss potential analytical and governing strategies and offer perspectives on how to improve critical Arctic infrastructure against various human and natural threats. The book is organized in three sections according to topical group and plenary discussions at the meeting on: cybersecurity infrastructure and threats, analytical strategies for infrastructure threat absorption and resilience, and legal frameworks and governance options to promote cyber resilience. Summaries and detailed analysis are included within each section as summary chapters in the book.00The book provides a background on analytical tools relevant to risk and resilience analytics, including risk assessment, decision analysis, supply chain management and resilience analytics. It will allow government, native and civil society groups, military stakeholders, and civilian practitioners to understand better on how to enhance the Arctic?s resilience against various natural and anthropogenic challenges.